Atypical chest pain as a prelude to cancer: an uncommon presentation of adenoid cystic carcinoma of the parotid gland - Jian Ho, Alex Zxi; Johari, Ahmad Hafizuddin; Ahmad Affandi, Khairunisa; Leman, Wan Ishlah (University of Toronto, 2025)
Adenoid cystic carcinoma (ACC) of the parotid gland is a rare malignancy characterized by delayed distant metastasis, often presenting as pre-auricular swelling. We report a 47-year-old male who initially presented with unexplained right-sided chest pain, leading to the discovery of a rib lesion and eventual diagnosis of metastatic ACC. Imaging revealed a parotid mass and metastatic involvement of the ribs, confirmed by biopsy. A left subtotal parotidectomy was performed, with histopathological examination confirming ACC. The patient received adjuvant radiotherapy and is stable with no recurrence at the 6-month follow-up. This case underscores the importance of considering head and neck cancers, including ACC, in patients with unexplained chest pain, especially those with a history of salivary gland tumours. Despite ACC's relatively low rate of regional lymph node metastasis, its propensity for distant metastasis, including to uncommon sites such as the ribs, highlights the need for a systematic approach in evaluating atypical presentations. Early detection through self-examination, clinical vigilance, and imaging modalities like PET-CT can significantly improve outcomes. Prolonged surveillance is crucial due to the risk of delayed metastasis. Prompt management in patients with atypical symptoms, such as chest pain, is essential for improving prognosis and patient survival